The Influence of Training and Career Development on Employee Performance at Bank Mandiri Retail Collection and Recovery Unit Regional Java Bali - Dramendra Pasaribu; Bobby W. Saputra (Journal of Social Research, 2025)
This research investigates the impact of training and career development on employee performance at Bank Mandiri Retail Collection and Recovery Unit in the Java Bali Region. The study aims to analyze the influence of training programs, career development initiatives, and their combined effect on employee performance within the organization. A quantitative associative approach was employed, utilizing data collected from employees through questionnaires and processed using statistical analysis tools. The findings reveal that training has a significant positive effect on employee performance, underscoring the importance of continuous skill enhancement to meet organizational goals. However, the study indicates that career development alone does not significantly influence employee performance, suggesting that other factors may play a more critical role. The combined effect of training and career development shows a substantial positive impact, highlighting the necessity for integrated human resource strategies to boost productivity and performance. This research contributes to the existing literature on human resource management and provides practical insights for Bank Mandiri and similar institutions, emphasizing the need for targeted training programs and holistic career development frameworks to enhance workforce efficiency.